A Rhesus Macaque Rhadinovirus Related to Kaposi’s Sarcoma-Associated Herpesvirus/Human Herpesvirus 8 Encodes a Functional Homologue of Interleukin-6 - Kaleeba, Johnan A. R. (American Society for Microbiology, 1999)
The rhesus rhadinovirus strain 17577 (RRV strain 17577) genome is essentially colinear with human herpesvirus 8 (HHV8)/Kaposi’s sarcoma-associated herpesvirus (KSHV) and encodes several analogous open reading frames (ORFs), including the homologue of cellular interleukin-6 (IL-6). To determine if the RRV IL-6-like ORF (RvIL-6) is biologically functional, it was expressed either transiently in COS-1 cells or purified from bacteria as a glutathione S-transferase (GST)-RvIL-6 fusion and analyzed by IL-6 bioassays. Utilizing the IL-6-dependent B9 cell line, we found that both forms of RvIL-6 supported cell proliferation in a dose-dependent manner. Moreover, antibodies specific to the IL-6 receptor (IL-6R) or the gp130 subunit were capable of blocking the stimulatory effects of RvIL-6. Reciprocal titrations of GST-RvIL-6 against human recombinant IL-6 produced a more-than-additive stimulatory effect, suggesting that RvIL-6 does not inhibit but may instead potentiate normal cellular IL-6 signaling to B cells. These results demonstrate that RRV encodes an accessory protein with IL-6-like activity.